2023
DOI: 10.1002/admi.202202368
|View full text |Cite
|
Sign up to set email alerts
|

Pd Thickness Optimization on Silicate Sheets for Improving Catalytic Activity

Abstract: Formic acid, nonetheless, has become a favorite for energy production [3] because of its facile processing and high hydrogen reservoir capacity. [3b] A prevalent class of catalysts for the dehydrogenation of formic acid is based on Pd nanomaterials [4] that efficiently dehydrogenate formic acid to hydrogen and carbon dioxide. Although tremendous efforts have been dedicated to improving Pd-based catalysts, [5] such as the catalytic activities of the Pd's crystal planes, [6] some critical mechanistic aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Our previous studies about Pd thickness optimization on silicate sheets show that such a particle size can exhibit excellent metallicity and catalytic activity. 10 The recovered SiO 2 −NH 2 /Pd SA from the first run, in which the Pd SA is converted into nanoparticles, exhibits a higher activity than that of the initial sample. Eventually, the catalytic activity stabilizes in the further runs under identical reaction conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Our previous studies about Pd thickness optimization on silicate sheets show that such a particle size can exhibit excellent metallicity and catalytic activity. 10 The recovered SiO 2 −NH 2 /Pd SA from the first run, in which the Pd SA is converted into nanoparticles, exhibits a higher activity than that of the initial sample. Eventually, the catalytic activity stabilizes in the further runs under identical reaction conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…8,9 In our recent investigation, we demonstrated that the thickness of Pd plate-like nanoparticles on any given support should be investigated to find the optimal catalytic performance since the optimal Pd thickness to deliver maximum catalytic activity depends on the type of the support and its surface chemistry. 10 However, how a functional group can influence Pd's electronic structure in conjunction with the support material has rarely been investigated. Additionally, the interdependence of stability and catalytic activity is another point that requires careful investigation in the case of Pdsupported catalysts possessing a functionalized surface.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To address the effect of the numbers of layers on the activity of the catalyst, Doustkhah et al reported that silicate sheets with six atomic layers of palladium with approximately 1 nm thickness, showed higher activities in the selective dehydrogenation of formic acid for hydrogen production in water compared to isotropic palladium nanoparticles and a single-atom palladium catalyst. [64] Zenobi et al used tipenhanced Raman spectroscopy to visualize the active sites of a (sub)monolayer of palladium deposited on the surface of Au (111) with the aim of a better understanding of the reaction mechanism. [65] The results indicated that for the hydrogenation of chloronitrobenzenethiol, the reactive regions are not limited on the palladium regions, but extend up to ~20 nm into the gold regions as a result of hydrogen spillover.…”
Section: Reviewmentioning
confidence: 99%